Ketogenic diet in clinical populations—a narrative review - Zemer, Alon; Samaei, Shabnam; Yoel, Uri; Biderman, Aya; Pincu, Yair (Frontiers in Medicine, 2024)
Ketogenic diet (KD) is a high-fat, low-carbohydrate (CHO) diet, designed to induce a metabolic state of ketosis in which the body metabolizes primarily lipids for energy production. Various forms of KD are being promoted as promising treatments for numerous health conditions from chronic headaches to weight-loss and even different forms of cancer and are becoming increasingly more popular. KD appears to be an efficacious approach for weight-loss, and maintenance, improved glycemia, cognitive function and cancer prognosis. However, there is a controversy regarding the safety of KD, and the potential health risks that might be associated with long-term exposure to KD.There is a gap between the acceptance and utilization of KD in individuals with health conditions and the criticism and negative attitudes towards KD by some clinicians. Many individuals choose to follow KD and are encouraged by the positive results they experience. Although the medical establishment does not endorse KD as a first line of treatment, clinicians need to be informed about KD, and offer support and medical supervision for patients who self-select to follow KD. This can ensure that within the boundaries of KD, patients will make good and healthy dietary choices and prevent clinical disengagement in extreme cases. To that end, there is an urgent need for good quality research to address the issues of long-term safety of KD in different clinical populations and for standardization of KD both in research and in the clinic.